A taxonomy of effective leader behaviors in the construction industry - Cabrera-Caban, Enrique (ProQuest Dissertations & Theses, 2016)
The construction industry is a major part of the United States economy, but it is also one of the most dangerous and high-risk industries. The industry is currently facing a shortage of effective leadership, and leaders face unique challenges in coordinating multiple teams of subcontractors on projects. The first step in remedying this shortage is to identify the behaviors of an effective construction leader. To address this need, a taxonomy of effective leader behaviors in construction was developed using grounded theory methodology and rated by construction industry subject matter experts. Archival focus group data from 10 focus groups in three regions of the United States with 66 construction employees including plumbers, pipefitters, safety directors, superintendents, and training instructors were analyzed in the first phase of the study using a grounded theory methodology and subsequently compared to extant construction leadership literature. In the second phase, the validity of the derived taxonomy was assessed in two studies: (1) five doctoral student subject matter experts performed a deductive content analysis and intercoder agreement was found to be acceptable, and (2) 39 construction managers rated the importance and relevance of each of the 36 taxonomy categories along with 3 categories of construction manager behaviors. Overall interrater agreement was acceptable, although low agreement was observed in several taxonomy categories. Mean ratings were compared between taxonomy and construction manager categories using t tests and were found to be significantly different. A comparison to extant leader behavior taxonomies demonstrated similarities and differences to the present taxonomy. Evidence from the present study demonstrates the uniqueness of the construction industry context for studying leadership and can be of use to researchers as an empirically supported framework of effective leader behaviors in construction, and to practitioners for training, selection, and performance evaluation.